A tetraphenylethene-based hexacationic molecular cage with an open cavity. Issue 96 (16th November 2022) - Cao, Fan; Duan, Honghong; Li, Qingfang; Cao, Liping
Abstract : A tetraphenylethene-based hexacationic molecular cage with an open cavity exhibited 1 : 2 or 1 : 1 host–guest recognition for nicotinamide adenine dinucleotides with dual responses of CD and fluorescence in water. Abstract : A tetraphenylethene-based hexacationic molecular cage (1) with an open cavity was synthesized. 1 exhibited 1 : 2 or 1 : 1 host–guest recognition for two nicotinamide adenine dinucleotide molecules (NADH and NAD + ) with different CD and fluorescence responses in water.